CLIMATE ELEMENTS AND FIRE HAZARD INDEXES IN SANTA CATARINA - Kossoski, Marcos Cesar; Muza, Michel Nobre; Vitor, Adriano; Quadro, Mario Francisco Leal de (Floresta, 2024)
Forest fires have caused significant environmental and economic damage over the years. In this context, efforts have been made to establish relationships between climate and control measures for fire occurrence. Assigning a fire danger index based on meteorological conditions is a way to provide tools for organizations responsible for forest fire prevention and combat. In this study, computational and statistical techniques were employed to analyze the performance of three fire hazard indices: the Monte Alegre Formula, the Altered Monte Alegre Formula, and the Ängstrom Risk Factor, for the state of Santa Catarina, located in the Southern region of Brazil. The study and validation period covered from 2010 to 2022, using variables such as precipitation, relative humidity, wind speed, and air temperature, with values obtained from the National Institute of Meteorology (INMET), encompassing 23 meteorological gauges. These data were compared with fire detection records obtained from satellite imagery and provided by the National Institute for Space Research (INPE). After analyzing the data using various statistical techniques, it became evident that both Monte Alegre Formulas exhibited a high accuracy rate for days with detected fire occurrences, with over 80% accuracy, compared to only around 35% for Ängstrom. Concerning the overall number of days computed, Ängstrom achieved a higher accuracy rate (approximately 85%), compared to values around 50% for both Monte Alegre Formulas.